2016
DOI: 10.1103/physrevb.93.045312
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Dirac and quantum spin Hall states in fluorinated monolayer As and AsSb

Abstract: Using first-principles calculations, we investigate the electronic and vibrational properties of monolayer As and AsSb. While the pristine monolayers are semiconductors (direct band gap at the point), fluorination results in Dirac cones at the K points. Fluorinated monolayer As shows a band gap of 0.16 eV due to spin-orbit coupling, and fluorinated monolayer AsSb a larger band gap of 0.37 eV due to inversion symmetry breaking. Spin-orbit coupling induces spin splitting similar to monolayer MoS 2 . Phonon calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…Such planarization could induce unique electronic properties. The functionalized arsenene AsR nanosheets, which are terminally decorated with R=H, F, Cl, Br, I, O, OH, CH 3 , etc, have aroused particular interests …”
Section: Surface Functionaliaztionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such planarization could induce unique electronic properties. The functionalized arsenene AsR nanosheets, which are terminally decorated with R=H, F, Cl, Br, I, O, OH, CH 3 , etc, have aroused particular interests …”
Section: Surface Functionaliaztionmentioning
confidence: 99%
“…Subsequently, Zhang et al have demonstrated that the fluorinated monolayer has a bandgap of 0.16 eV due to the SOC and the topologically nontrivial state, which is in sharp contrast to the monolayer AsSb . They have investigated the atomically thin β‐SbAs polymorph and found that the SOC effect is significant, leading to reduction of about 200 meV in its band gap . Moreover, the bandgap of β‐SbAs was able be closed and reopened by using biaxial tensile strain, with the topological invariant Z 2 = 1.…”
Section: Potential Applicationsmentioning
confidence: 99%
See 3 more Smart Citations